Error analysis of tissue resistivity measurement - Tsai, Jang Zern; Will, James A.; Stelle, Scott Hubbard Van; Cao, Hong; Tungjitkusolmun, Supan; Choy, Young Bin; Haemmerich, Dieter; Vorperian, Vicken R.; Webster, John G. (My University, 2002)
We identified the error sources in a system for measuring tissue resistivity at eight frequencies from 1 Hz to 1 MHz using the four-terminal method. We expressed the measured resistivity with an analytical formula containing all error terms. We conducted practical error measurements with in-vivo and bench-top experiments. We averaged errors at all frequencies for all measurements. The standard deviations of error of the quantization error of the 8-bit digital oscilloscope with voltage averaging, the nonideality of the circuit, the in-vivo motion artifact and electrical interference combined to yield an error of ±1.19%. The dimension error in measuring the syringe tube for measuring the reference saline resistivity added ±1.32% error. The estimation of the working probe constant by interpolating a set of probe constants measured in reference saline solutions added ±0.48% error. The difference in the current magnitudes used during the probe calibration and that during the tissue resistivity measurement caused ±0.14% error. Variation of the electrode spacing, alignment, and electrode surface property due to the insertion of electrodes into the tissue caused ±0.61% error. We combined the above errors to yield an overall standard deviation error of the measured tissue resistivity of ±1.96%.
Keywords: Calibration; Electrode; Error analysis; Error measurement; Four terminals; Noise measurement; Probe constant; Tissue resistivity